2000
DOI: 10.1016/s0886-3350(00)00366-7
|View full text |Cite
|
Sign up to set email alerts
|

Nonpenetrating filtration surgery for glaucoma: Control by surgery only

Abstract: Nonpenetrating filtration surgery in eyes with POAG was more rewarding in untreated patients than in medically treated patients. To control IOP without medication, revision of the filtration site is feasible and needed in the medium and long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
1
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 14 publications
3
36
1
1
Order By: Relevance
“…However, the distal collector system may have a better chance of survival if intervention is undertaken earlier in the disease process, before the outflow system collapses or before chronic topical medical therapy negatively impacts the tissues [28,29]. The excellent safety profile of canaloplasty or other non-penetrating surgery may make such procedures an earlier option in many instances, such as in younger patients where cataract formation is of concern, where medical therapy has proven insufficient, or the conjunctiva is not suitable for bleb formation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the distal collector system may have a better chance of survival if intervention is undertaken earlier in the disease process, before the outflow system collapses or before chronic topical medical therapy negatively impacts the tissues [28,29]. The excellent safety profile of canaloplasty or other non-penetrating surgery may make such procedures an earlier option in many instances, such as in younger patients where cataract formation is of concern, where medical therapy has proven insufficient, or the conjunctiva is not suitable for bleb formation.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly fewer eyes treated with 364 Dahan and Drusedau demonstrated that the non-penetrating surgery in eyes previously treated was 4.7 times less efficacious than in untreated eyes [5]. Sunaric-Mégevand and Leuenberger conducted a prospective study on a consecutive series of 67 eyes of 67 patients with preoperative maximal tolerance medical therapy, and reported a 88% overall success rate and a 68% complete success rate at 1 year [22].…”
Section: Discussionmentioning
confidence: 99%
“…In many published series postoperative goniopuncture is performed with a Nd : YAG laser which transform a nonpenetrating operation to a penetrating one. [15][16][17][18][19][20][21] A few prospective studies comparing standard trabeculectomy and NPT have been published. In prospective randomised clinical trials El-Sayyad et al 3 and Lachkar et al 22 randomly assigned patients to receive deep sclerectomy in one eye and trabeculectomy on the other eye.…”
Section: -14mentioning
confidence: 99%